The efficacy of the well of the well (WOW) culture system on development of bovine embryos in a small group and the effect of number of adjacent embryos on their development. Issue 3 (June 2015) - Kang, Sung-Sik; Ofuji, Sosuke; Imai, Kei; Huang, Weiping; Koyama, Keisuke; Yanagawa, Yojiro; Takahashi, Yoshiyuki; Nagano, Masashi
Summary The aim of the present study was to clarify the efficacy of the well of the well (WOW) culture system for a small number of embryos and the effect of number of adjacent embryos in a WOW dish on blastocyst development. In conventional droplet culture, embryos in the small-number group (5–6 embryos/droplet) showed low blastocyst development compared with a control group (25–26 embryos/droplet). However, small and large numbers of embryos (5–6 and 25 embryos, respectively) in a WOW dish showed no significant differences in cleavage, blastocyst rates, and mean cell number in blastocysts compared with the control group (25–30 embryos/droplet). In addition, the number of adjacent embryos in a WOW dish did not affect the development to blastocysts and cell number in blastocysts. In conclusion, a WOW dish can provide high and stable blastocyst development in small group culture wherever embryos are placed in microwells of the WOW dish.